Expert System for Tomato Plant Pest Diagnosis Using the Certainty Factor Method - Annafi Franz; Sri Ngapiyatun; Sulpiana (TEPIAN, 2020)
This research is motivated by the failure of tomato harvest one of which is a pest attack for that program will be carried out to identify pest attacks so that crop failure can be avoided. This expert system will be implemented with the certainty factor method can provide accurate results obtained from calculations based on the weight of the symptoms chosen by the user, able to provide answers to problems that are not certain of truth such as problems diagnosing disease risk, and with this method, the expert illustrates the confidence of an expert with giving the weight of confidence in accordance with relevant expert knowledge. so that researchers increasingly believe that this expert system will be easily accessible and used by the community. From the explanation above for that, the writer makes a system, namely expert system for diagnosing oil palm plant diseases using the certainty factor method which is intended to assist the work of farmers in providing information and conclusions from pests suffered on oil palm plants.